2018
DOI: 10.1002/jia2.25051
|View full text |Cite
|
Sign up to set email alerts
|

Linkage and retention in HCV care for HIV‐infected populations: early data from the DAA era

Abstract: IntroductionThere is currently no published data on the effectiveness of DAA treatment for elimination of HCV infection in HIV‐infected populations at a population level. However, a number of relevant studies and initiatives are emerging. This research aims to report cascade of care data for emerging HCV elimination initiatives and studies that are currently being evaluated in HIV/HCV co‐infected populations in the context of implementation science theory.Methods HCV elimination initiatives and studies in HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 56 publications
3
28
0
Order By: Relevance
“…As treatment is costly and treatment uptake varies considerably across countries , effective behavioural interventions for MSM at risk of (re‐)infection are urgently needed. Qualitative research among HIV‐positive MSM with a cured HCV infection in the pre‐DAA era showed that the strongest motive to implement risk reduction strategies was the reward of avoiding HCV retreatment and its side effects , but this may have changed with the less burdensome DAA treatment. Also sexual risk norms within the MSM population, HCV stigma and non‐disclosure of HCV status forms barriers to safer sex, and drug use directly impedes the self‐efficacy of MSM to take risk reduction measures .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As treatment is costly and treatment uptake varies considerably across countries , effective behavioural interventions for MSM at risk of (re‐)infection are urgently needed. Qualitative research among HIV‐positive MSM with a cured HCV infection in the pre‐DAA era showed that the strongest motive to implement risk reduction strategies was the reward of avoiding HCV retreatment and its side effects , but this may have changed with the less burdensome DAA treatment. Also sexual risk norms within the MSM population, HCV stigma and non‐disclosure of HCV status forms barriers to safer sex, and drug use directly impedes the self‐efficacy of MSM to take risk reduction measures .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several studies evaluating the effect of behavioural and/or testing interventions with prompt treatment, on HCV incidence among HIV‐positive MSM have been initiated . “Real‐life” settings in the Netherlands and Switzerland showed that high uptake of DAA among HIV‐HCV co‐infected MSM in clinical care, in Switzerland combined with intensive HCV‐RNA screening and behavioural intervention, was followed by a reduction in HCV incidence .…”
Section: Methodsmentioning
confidence: 99%
“…In order to design and evaluate interventions that seek to improve linkage to HCV care following release, an understanding of the barriers and facilitators to care should be explored. However, up until the recent DAA era, research to improve linkage to HCV care has been rarely undertaken for people released from prison . That said, because individuals incarcerated with HCV share similar sociodemographic and psychosocial characteristics as incarcerated HIV‐positive individuals, exploring barriers and facilitators to HIV care following release—care that now dates back several decades—may help advance HCV linkage to care strategies and related research .…”
Section: Introductionmentioning
confidence: 99%
“…HIV coinfected). Sacks‐Davis and colleagues have gathered data from numerous local and national initiatives working towards HCV elimination in HIV coinfected populations globally . They show that while treatment has increased substantially in the era of DAAs (mostly in high‐income countries) two‐thirds of people still have not accessed treatment.…”
Section: Introductionmentioning
confidence: 99%